Endothermic and exothermic reactions and stagnation point nanofluid flow over a porous stretched surface with a revised Buongiorno model - R.P. Ashrith; K.V. Nagaraja; P. Nimmy; Pinank Patel; Ankur Kulshreshta; J.K. Madhukesh; Chander Prakash (South African Journal of Chemical Engineering)
Advancements in advanced nanotechnology have significantly enhanced the thermal implications of nanoparticles, given their increasing importance in engineering and thermal extrusion systems.Understanding the behavior of biological systems, improvement in industrial processes, and technological development, as well as understanding activation energy in endothermic/exothermic reactions, is crucial nowadays. Thus, the present work aims to assess exothermic or endothermic chemical processes with the activation energy on nanofluid flow along a stretched surface, accounting for Brownian motion and thermophoresis effects. The fourth fifth-order scheme of the Runge Kutta Fehlberg method approach was used to solve the PDEs after they were converted into ODEs using similarity variables. According to the study, the velocity profile increases with velocity ratio parameter values. As chemical reaction and thermophoresis parameters are raised, the temperature falls for endothermic reactions and rises for exothermic reactions; however, the pattern is opposite when the Brownian motion and activation energy parameters are increased. The concentration profile boosts with the thermophoresis parameter and drops as the Brownian motion parameter increases. Skin friction remains constant across various parameters, but heat and mass transfer exhibit variations. The present study provides valuable insights with various practical applications in distinct sectors such as industrial chemical processes, biomedical engineering, thermal management systems, environmental management, energy systems, and environmental engineering.